2016
DOI: 10.1007/s11695-016-2252-7
|View full text |Cite
|
Sign up to set email alerts
|

Re-operations after Secondary Bariatric Surgery: a Systematic Review

Abstract: This paper reviews reoperations rates for short- and long-term complications following secondary bariatric procedures and need for further bariatric surgery. The search revealed 28 papers (1317 secondary cases) following at least 75 % of patients for 12 months or more. For adjustable gastric banding (AGB), rebanding had higher re-revisional rates than conversions into other procedures. Conversion of AGB to Roux-en-Y gastric bypass had the highest number of short- (10.7 %) and long-term (22.0 %) complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
2
19
0
6
Order By: Relevance
“…Bariatric surgery has proven to effectively treat morbid obesity and its comorbidities [1,2]. However, in 20-30% of the bariatric population insufficient weight loss (< 50% excess weight loss) or substantial weight regain is observed; both can lead to re-emerging of comorbidities and secondary and/ or tertiary bariatric procedures [3][4]. Behavioural factors can be modified and thereby reoperations could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery has proven to effectively treat morbid obesity and its comorbidities [1,2]. However, in 20-30% of the bariatric population insufficient weight loss (< 50% excess weight loss) or substantial weight regain is observed; both can lead to re-emerging of comorbidities and secondary and/ or tertiary bariatric procedures [3][4]. Behavioural factors can be modified and thereby reoperations could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptualisation and construction phase of a health economic model could, for example, take into consideration that patients who are experiencing financial distress are at a higher risk of seeking ongoing bariatric surgical care (such as complications and reoperations) in the public health care system. In regard to potential complications and reoperations, recent evidence has found that complications and/or reoperations can cost as much as the primary procedure itself and that the estimated rates (particularly after secondary bariatric surgery) are higher than the usually reported risks (Campbell, Venn, et al, ; Kuzminov, Palmer, Wilkinson, Khatsiev, & Venn, ). In turn, some of these participants may allow their private health insurance to lapse if they experience even more financial hardship, increasing likelihood of future presentations for complications and reoperations through the public sector.…”
Section: Discussionmentioning
confidence: 99%
“…O reganho é um desfecho negativo complexo que geralmente ocorre em longo-prazo. A revisão cirúrgica não é padronizada e acarreta considerável morbimortalidade com piores desfechos quando comparada ao procedimento primário (Brethauer et al, 2014;Kuzminov et al, 2016). Assim, por ser menos invasivo, o tratamento endoscópico torna-se uma opção oportuna.…”
Section: Discussionunclassified
“…Por vezes, este é um doente que se apresenta tão ou mais obeso que no procedimento índice, mais velho, com mais tempo de doença e com o fator complicador do antecedente bariátrico que dificulta uma nova intervenção cirúrgica (Brethauer et al, 2014;Kuzminov et al, 2016). Estes fatores possivelmente explicam as maiores taxas de complicações da cirurgia bariátrica secundária.…”
Section: Discussionunclassified
See 1 more Smart Citation